Demographic and clinical characteristics of patients with spinal cord injuries: Two years’ experience at a tertiary rehabilitation center (Annals of Medical Research, 2021)
None
Keywords: s: Spinal Cord Injury; Demographics; Tertiary Rehabilitation Center.